(untitled) (Journal of Educational Sciences, 2019)
The article considers the main directions of development of the educational environment with the use of modern information technologies, describes the problem of improving the quality of education, bringing it in line with international standards. The modern educational paradigm is not focused on the knowledge acquisition, but the application of this knowledge, the formation of functional literacy. A new generation of students can easily master any innovations in digital and multimedia technology. The article describes the main task that is set for the teacher - to stimulate and guide the student and the student in development. Therefore methods of working with students are being actively improved, test techniques are applied. The article defines the concept of pedagogical technology as an information technology, since the basis of the technological process of education is the receipt and transformation of information. It is revealed that for the formation of functional literacy it is necessary to create a special educational environment for students, not only in the classroom, but also in after-hours. To do this, we need to proceed from what functional literacy is. In addition, it is necessary to consider the means of forming functional literacy. It is established that students have significant difficulties in applying the mathematical apparatus to solving applied problems; Some schoolchildren do not see the connection between mathematical theory and practice. As part of the study, a pedagogical experiment was conducted to introduce new methods of teaching mathematics using ICT. Key words: education, mathematical education, information technologies, educational environment, experiment.